A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Association mapping reveals loci associated with multiple traits that affect grain yield and adaptation in soft winter wheat - Dennis N. Lozada; R. Esten Mason; Md Ali Babar; Brett F. Carver; Gina-Brown Guedira; Keith Merrill; Maria Nelly Arguello; Andrea Acuna; Lucas Vieira; Amanda Holder; Christopher Addison; David E. Moon; et al. (Euphytica, 2017)

Local population differentiation in Bromus tectorum L. in relation to habitat-specific selection regimes - Jason W. Scott; Susan E. Meyer; Keith R. Merrill; Val J. Anderson (Evolutionary Ecology, 2010)

Genetic variation and local adaptation at a cheatgrass ( Bromus tectorum ) invasion edge in western Nevada - ELIZABETH A. LEGER; ERIN K. ESPELAND; KEITH R. MERRILL; SUSAN E. MEYER (Molecular Ecology, 2009)
Cheatgrass ( Bromus tectorum ) is an invasive weed in western North America found primarily growing at elevations less than 2200 m. We asked whether cheatgrass is capable of becoming adapted to a marginal habitat, by investigating a population at a high elevation invasion edge. We used a combination of methods, including reciprocal field transplants, controlled environment studies and molecular analysis. High levels of SSR gene diversity (0.50 vs. 0.43) and comparable variation in phenotypic traits were observed at both the invasion edge and a low elevation, high‐density population. Three heterozygotes were observed in the edge population, which is unusual in this predominantly self‐pollinating plant. Plants from high elevations germinated more slowly in a growth chamber and had slower seedling growth rates. Survivorship was low at the edge (13%), compared with the low elevation site (55%), but surviving plants were of similar size and had equivalent reproductive output. Seed size positively affected survival and plant performance in the field and this trait was inherited. Emergence timing affected survival at the low elevation site and germination timing was also inherited. Local adaptation was seen in the low, rather than in the high elevation site, because of differential survival. While there was no evidence for local adaptation to the high elevation site observed in the field, family level and genotype‐level differences in traits that affected field performance, high genetic diversity at the invasion edge, and evidence of outcrossing in this highly selfing species indicates that the potential for adaptation to a marginal habitat exists within this population.